Ecosystem startups in kazakhstan (Herald of Journalism, 2019)
The scientific article sets out the definition of ecosystems, the findings of scientists. At the same time, a scientific analysis was made of topical issues such as global warming, causes and effects of climate change and problems related to national ecosystems, intensive development of the resources of the Caspian Sea shelf, pollution and water pollution.The purpose of the article is to review the impact of air pollution in Kazakhstan on the implementation of measures to solve these problems and to analyze the content of legislative documents adopted in the Republic of Kazakhstan in solving global environmental problems.An academic review of the writing skills of environmental journalists is given, based on the scientific and geographical value of the study, as well as the form and content of the materials delivered. The article also outlines issues that journalists should pay attention to when preparing material on the subject of ecology, and which areas should be taken into account when studying the subject.The main result of the article is to prevent problems in the field of ecology, the interaction of the media and ordinary people. The article describes the launch of an ecosystem initiative.The value of the book lies in the fact that the author focuses on the implementation of ecosystem initiatives in different countries of the world. Despite the relationship and interest between investors and startups, the ultimate goal is to earn a living for development. Local investors understand that start-ups are not short-term, but that they will happen quickly, but they are successful investors. Startups are also expected not only to raise funds, but also to participate in the beginner’s life, as entrepreneurs often have only the product.
Keywords: ecosystem, climate, ecological information, global warming.